If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 4(t + -9) = 2(t + 6) + 5 Reorder the terms: 7 + 4(-9 + t) = 2(t + 6) + 5 7 + (-9 * 4 + t * 4) = 2(t + 6) + 5 7 + (-36 + 4t) = 2(t + 6) + 5 Combine like terms: 7 + -36 = -29 -29 + 4t = 2(t + 6) + 5 Reorder the terms: -29 + 4t = 2(6 + t) + 5 -29 + 4t = (6 * 2 + t * 2) + 5 -29 + 4t = (12 + 2t) + 5 Reorder the terms: -29 + 4t = 12 + 5 + 2t Combine like terms: 12 + 5 = 17 -29 + 4t = 17 + 2t Solving -29 + 4t = 17 + 2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-2t' to each side of the equation. -29 + 4t + -2t = 17 + 2t + -2t Combine like terms: 4t + -2t = 2t -29 + 2t = 17 + 2t + -2t Combine like terms: 2t + -2t = 0 -29 + 2t = 17 + 0 -29 + 2t = 17 Add '29' to each side of the equation. -29 + 29 + 2t = 17 + 29 Combine like terms: -29 + 29 = 0 0 + 2t = 17 + 29 2t = 17 + 29 Combine like terms: 17 + 29 = 46 2t = 46 Divide each side by '2'. t = 23 Simplifying t = 23
| 12s^2+s-35= | | 9=5x+6 | | 4944=48(-32+x) | | x(x-9)+20=0 | | 980=-98p | | p(t)=-3t^2-7t-8 | | x+(x+13)=54 | | x=0.8x+2.8 | | 4a^2-144=0 | | 6p=228 | | 5-x-2=3 | | x=6x+3x | | 10x+6=2x+44 | | 6+4(1+3x)=7(x-5) | | 55=-7x+6 | | -1.4(-4p-1)+4.4p= | | 9y-3=7y+1 | | 4x+7=7(x+1)-3x | | 26-(3x-10)=6 | | 4-36= | | -4+-61= | | -1.4(-4p-1)+4.4= | | d+9-90=-5 | | -2(4-3z)-7=6(z+1) | | 2x-(24-x)=-6 | | 20x+5=125 | | 2(5t-1)=10-2t | | x(x+1)=552 | | 4(x-2)-6x=35 | | 3x-x=30 | | 4x-3=28x+3 | | 3(2x+1)-8= |